1999
DOI: 10.1159/000040986
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Thrombopoietin Concentrations in Response to Platelet Transfusion Therapy

Abstract: Studies performed in rabbit and mouse models and in a limited number of human subjects, show that transfused platelets bind thrombopoietin (TPO) and decrease its concentration in the circulation. The aim of the present study was to further examine this relationship. The material comprised 12 patients receiving a total of 21 transfusions, as part of the routine clinical treatment. Blood samples were collected from the patients immediately before and 30 min after completion of the platelet transfusion, and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
3
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
3
3
0
Order By: Relevance
“…In the current study, it was shown, in accordance with previous findings, that, upon platelet transfusion, the plasma TPO concentration declines 16–18 . As in patients undergoing chemotherapy, who have fluctuating platelet counts, an inverse correlation was found between platelet count and TPO concentration.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current study, it was shown, in accordance with previous findings, that, upon platelet transfusion, the plasma TPO concentration declines 16–18 . As in patients undergoing chemotherapy, who have fluctuating platelet counts, an inverse correlation was found between platelet count and TPO concentration.…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings were reported in mouse models 4 . We 12 and others 17,18 showed that, in humans with thromb ocytopenia, the elevated plasma TPO concentration decreases upon platelet transfusion. In vitro studies, in which radiolabeled TPO was presented to human platelets, showed that platelets did indeed bind TPO.…”
supporting
confidence: 85%
“…Platelet transfusions may affect the endogenous production of platelets, because the primary stimulator of thrombopoiesis, thrombopoietin, is cleared from circulation by internalization and degradation via receptor‐mediated uptake in the platelets 20, 21. Platelet transfusions may therefore bias the results when studying changes in IPF in thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Another benefit of low dose platelet therapy may be an earlier return of autologous platelet production in thrombocytopenic patients following chemotherapy or bone marrow transplantation. As platelets express the thrombopoietin receptor on their surface and transfused platelets have been documented to adsorb thrombopoietin [46,47], it is possible that lower dose platelet therapy may shorten the duration of thrombocytopenia. If thrombopoietin levels are not reduced by high‐dose platelet transfusions, more thrombopoietin would be available to stimulate autologous platelet production once megakaryocytopoiesis returns.…”
Section: Relationship Between Platelet Count and Bleeding Risk: Implimentioning
confidence: 99%